Photocatalytic dye degradation under sunlight irradiation using cerium ion adsorbed two-dimensional graphitic carbon nitride. Issue 4 (August 2020) - Kuila, Saikat Kumar; Sarkar, Ranjini; Kumbhakar, Partha; Kumbhakar, Pathik; Tiwary, Chandra Sekhar; Kundu, Tarun Kumar
Graphical abstract: Highlights: Adsorption experiments and DFT simulation study suggest the chemisorption of Ce 3+ on 2D-g-C3 N4 . HR-TEM image shows the localized point defects and lattice alteration of Ce 3+ -g-C3 N4 . Experimental observations (HR-TEM/FTIR/XPS) are in well correspondence with simulated results. Ce 3+ -g-C3 N4 delays the recombination probability of photogenerated charge carriers and increases the fluorescence decay time. Optimized Ce 3+ -g-C3 N4 shows dye degradation efficiency upto 95 % in water under sunlight irradiation. Abstract: Unique optical, physicochemical and surface properties of two dimensional (2D) materials provide an enormous opportunity in environmental remediation. Those properties are further tuned by using external dopant or alloying elements. Due to their distinct optoelectronics properties, the rare earth elements and compounds act as a proficient dopant in combination with 2D materials. Here, 2D-g-C3 N4 accumulated with Ce 3+ (Ce 3+ -g-C3 N4 ) has been synthesized using simple and easily scalable ion-adsorption (chemical controlled) process. The spectroscopy and microscopy techniques have been utilized to understand the surface adsorption, optical properties and localized point defect formation due to decoration of Ce 3+ . Along with the experimental studies, first principles density functional theory (DFT) calculations have been performed to understand the structural and electronic behavior of Ce 3+ adsorption on 2D-g-C3 N4 . Ce 3+ -g-C3 N4 prepared using optimized condition is further utilized for removal of a pollutant, namely methylene blue dye from the water with 95 % efficiency even under sunlight. Also, Ce 3+ -g-C3 N4 shows an enhancement in photocatalytic degradation rate (∼20 %) as compared to 2D-g-C3 N4 . So the suggested photocatalyst can be used commercially in the field of pollutant degradation.